Towards Improving the Vegetative and Qualitative Traits of Sunflower Using Amending Soil (Zeolite and Manure Farmyard) under Water Deficit Stress. Issue 18 (11th October 2019) - Jami, Mohammad Ghasem; Baghbani-Arani, Abolfazl; Karami Borz- Abad, Rezvan; Saadatkhah, Atefe
ABSTRACT: The effect of different sources of nitrogen fertilizers (organic fertilizers and urea) and zeolite under different irrigation regime on the qualitative traits of sunflower seeds was investigated by a trial, in 2014 and 2015 in Iran with split factorial on a randomized complete block design with three replications. Main plots consisted of irrigation regimes (irrigation after unloading 40%, 60% and 80% of available soil water ( ASW )). The sub-plots consisted of factorial combinations of three nitrogen fertilizer treatments (100% organic, integrated treatment and 100% chemical treatment) and three levels of zeolite (10, 5 and 0 ton ha −1 ). Farmyard manure and urea were the organic and chemical sources of nitrogen, respectively; integrated treatment included 50% organic +50% chemical nitrogen. The percentage of nitrogen required by urea was set in a way that 100% of the required nitrogen could be provided by urea. The maximum diameter and stems height as well as the performance of the oil and protein by application of zeolite were measured in terms of the lack of stress in the first and second year, respectively. In sum, it can be concluded that the severe water stress can reduce the percentage of unsaturated fatty acids. In the first year, oleic acid and linoleic acid were decreased by 22% and 7%, respectively; while in the second year, they were reduced by 27% and 6.8%. Stearic acid also declined in the first and second years by 50% and 52%, respectively. However, an increase was observed for palmitic acid of sunflower. In both years, the application of organic fertilizer increased linoleic acid and oleic and improved the quality of sunflower seed oil. Under favorable irrigation conditions, organic fertilizers could be advantageous; while organic fertilizers and zeolite can be helpful under drought stress conditions.